Rotavirus infection among children under five years of age hospitalized with acute gastroenteritis in Myanmar during 2018–2020 – Multicentre surveillance before rotavirus vaccine introduction. Issue 47 (16th November 2021) - Myat, Theingi Win; Thu, Hlaing Myat; Tate, Jacqueline E.; Burnett, Eleanor; Cates, Jordan E.; Parashar, Umesh D.; Kyaw, Ye Myint; Khaing, Tin Ei Ei; Moh, Khin Moh; Win, Nwet Nwet; Khine, Win Kay; Kham, Myat Mo Zar; et al.
Highlights: This study describes rotavirus epidemiology before rotavirus vaccine introduction in Myanmar. Rotavirus detection was 45.7% in May 2018–Apr 2019 and 42.5% in May 2019–Jan 2020. The highest proportion of positivity was among 6–11 month old children (41.6%). Diversity of rotavirus strains over time before vaccine introduction was found. This study will be important baseline data for monitoring of vaccine impact. Abstract: Background: Rotavirus gastroenteritis (RVGE) is a leading cause of severe diarrhea in children under-five worldwide, with the majority of mortality in lower -income countries. This study aimed to provide baseline information on epidemiology of rotavirus and circulating strains before rotavirus vaccine introduction in Myanmar. Methods: Hospital-based, prospective surveillance was conducted from May 2018 to January 2020 at four sentinel sites; two hospitals in Lower Myanmar, one hospital each in Middle Myanmar and East Myanmar. Children under five years of age hospitalized for acute gastroenteritis were enrolled; demographic and clinical data were collected. Stool samples were screened by ELISA (ProSpecT™ Rotavirus, OXOID-UK) for rotavirus antigen and a subset of ELISA positive samples were genotyped by reverse transcription polymerase chain reaction. Results: Rotavirus was detected in 45.7% (799/1750) of cases enrolled at three sites in May 2018–April 2019 and 42.5% (521/1227) at four sites in May 2019–January 2020. RVGE cases were predominantly male (58.7%; 775/1320) and 92.6% (1223/1320) of RVGE cases occurred in <2 years old. Rotavirus detection was higher in the cold and dry season (November–April). RVGE compared to non-RVGE cases had more frequent vomiting (78.3% Vs 68.1%, p < 0.01), fever (65.8% Vs 61.3%, p = 0.01), severe dehydration (3.6% Vs 2.1%, p < 0.01) and requirement of treatment by IV fluid (58.3% Vs 53.1%, p < 0.01). The most prevalent genotypes identified were G1P[6] (113/359, 31.5%), G1P[8] (94/359, 26.2%) and G2P[4] (33/359, 9.2%). Conclusions: This study confirms the persistent high prevalence of RVGE among children under-five admitted to hospitals in different parts of Myanmar and the diversity of rotavirus strains over time prior to vaccine introduction. The rotavirus vaccine was introduced nationwide in February 2020 in Myanmar and these data will be important baseline data for post-vaccination monitoring of vaccine impact and circulating strains.